The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1140/epjd/e2010-10442-2
|View full text |Cite
|
Sign up to set email alerts
|

Production of entanglement in Raman three-level systems using feedback

Abstract: We examine the theoretical limits of the generation of entanglement in a damped coupled ioncavity system using jump-based feedback. Using Raman transitions to produce entanglement between ground states reduces the necessary feedback bandwidth, but does not improve the overall effect of the spontaneous emission on the final entanglement. We find that the fidelity of the resulting entanglement will be limited by the asymmetries produced by vibrations in the trap, but that the concurrence remains above 0.88 for r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…It turns out that Markovian quantum feedback can be used to increase the steady-state entanglement of the atoms [138][139][140][141][142][143][144][145][146][147][148][149][150][151]. It has been shown that this is possible using both feedback based on photon detections (quantum jumps) [145][146][147][148][149][150][151], and feedback using homodyne detection (trajectories driven by Gaussian noise) [138][139][140][141][142].…”
Section: Entanglement Creation and Controlmentioning
confidence: 99%
“…It turns out that Markovian quantum feedback can be used to increase the steady-state entanglement of the atoms [138][139][140][141][142][143][144][145][146][147][148][149][150][151]. It has been shown that this is possible using both feedback based on photon detections (quantum jumps) [145][146][147][148][149][150][151], and feedback using homodyne detection (trajectories driven by Gaussian noise) [138][139][140][141][142].…”
Section: Entanglement Creation and Controlmentioning
confidence: 99%
“…We enhance our scheme by combining the dissipative state preparation with the detection of photons. Improvement in state generation through conditional dynamics has been explored in schemes relying on feedback [20][21][22] and also used recently in [16]. Here we show that by conditioning the system dynamics to the detection of photons spontaneously emitted into the environment, we obtain a significant fidelity enhancement with detection efficiencies of 10%.…”
mentioning
confidence: 76%
“…The difference is that and are the ground states and mode A is non-local. It should be noted that Stevenson et al have also derived a similar model with two Raman three-level systems in the same cavity [ 36 ], but we will see below that the coupled-cavity array system is much useful for stabilizing different Bell states. The dissipative dynamics of the whole system is characterized by the Markovian master equation where the terms characterizing the spontaneous emission of atom has been neglected, since the atom is restricted in the subspace spanned by , .…”
Section: Effective Master Equation Of the Coupled-cavity Array Sysmentioning
confidence: 90%